Interpersonal Meaning in RAs: Some Traces of Modality - Wawan Hendrawan; Eva Tuckyta Sari Sujatna; Ekaning Krisnawati; Nani Darmayanti (TEKNOSASTIK, 2020)
Studies on interpersonal meaning have been well documented. However, few studies explored interpersonal meaning in the area of research articles. In responding to this, the present study tried to reveal interpersonal meaning in RAs’ discussion sections. The data taken were from five reputable international journals categorized in the subject of language and linguistics indexed by Scopus with the SJR value above one. Having been analyzed by using the theory of modality from Halliday (1994), the data demonstrated that three types of modality values were identified such as high, middle, and low. In addition, there were some disparities among the results investigated. If sequenced, the low outnumbered the middle and the high values. This suggested that the authors had different assessments towards the topics written.